Program Sosialisasi dan Edukasi Hukum tentang Perlindungan dan Pengelolaan Sumber Daya Alam di SMAN 2 Kampar Untuk Membangun Kesadaran Generasi Muda - Muhammad Fathan Pratama; Cintia M. Sianturi; Rani Aulina Siahaan; Nabila Putri Rosanty; Dwi Hamdila; Karina Patricia; Khoirunnisa Lubis; Rajwa Rahnia Putri; Sumisko Dasriwal (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
A legal outreach program on natural resource protection and management was implemented by KUKERTA MBKM students from the Faculty of Law, University of Riau, at SMAN 2 Kampar to raise awareness among young people about the preservation of the Ghimbo Potai customary forest. The program used pre-test and post-test methods with 70 of the 150 participants. Results showed a significant increase in understanding, from 22.86% of students before the outreach program to 92.8% after the program, representing a 69.94% increase in understanding. Through interactive lectures and participatory discussions, the program proved effective in increasing students' legal knowledge and awareness of the importance of sustainable natural resource management.